2012
DOI: 10.4172/2155-9899.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Contributing to Systemic Lupus Erythematosus in Tunisian Patients

Abstract: Systematic lupus erythematosus (SLE) is a multi system autoimmune disease characterized by autoantibodies production, multi-organ damage and complex genetic inheritance. Multiple genetic and environemental factors contribute to the pathogenesis of this disease. Recent genome-wide studies, have added substantially to the number of genes associated with SLE. We performed a case control study using 138 SNPs in 93 Tunisian patients affected with lupus and 162 healthy controls. All SNPs were genotyped in a Sequenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This was consistent with reports from adult patients with SLE from different ethnic groups; 17,3234 a report from Tunisia on SNPs in patients with SLE has shown its association with rs2004640 and rs10954213 ( P = 0.024 and P = 0.035, respectively). 21 From different studies, there is general model of inheritance in which individuals carrying one copy of the rs2004640 T allele are at increased risk for SLE, and individuals carrying two copies have an even higher relative risk. 17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was consistent with reports from adult patients with SLE from different ethnic groups; 17,3234 a report from Tunisia on SNPs in patients with SLE has shown its association with rs2004640 and rs10954213 ( P = 0.024 and P = 0.035, respectively). 21 From different studies, there is general model of inheritance in which individuals carrying one copy of the rs2004640 T allele are at increased risk for SLE, and individuals carrying two copies have an even higher relative risk. 17…”
Section: Discussionmentioning
confidence: 99%
“…Reports including pSLE patients and two of the studied SNPs (rs2004640 and rs10954213) are scarce, 14,21 while rs2280714 was not included in any studies with paediatric lupus patients to the best of our knowledge. The largest number of pSLE cases was published in 2007 by Reddy et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent genetic studies have reported an allelic association between IRF5 and SLE and a best association for the rs2070197 polymorphism [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 98%